Immediate Effects of Anesthesia Agents on Liver Function - Afaf Hmza,; Fatma Alashkham,; Abdalrheem Ammr,; Abdulwahhab Ashour,; Salah Aldeen Altwayr, (AlQalam Journal of Medical and Applied Sciences, 2024)
Anesthetic agents and types may deteriorate liver function; therefore, choosing anesthetics with less hepatotoxicity is important. The elevations of serum aminotransferase (AST), alanine transaminase (ALT), and alkaline phosphatase (ALP) levels are frequently observed after surgical procedures, whether performed under general or spinal (regional) anesthesia. Therefore, the study aimed to investigate and compare the changes in liver enzymes following general anesthesia and regional anesthesia. An observational sheet was used to obtain data from patients and then statistically analyzed using the IMB Statistical Package for Social Sciences (SPSS) Statistic software version (23). A significant difference in the liver enzymes levels change was determined with a p-value of < 0.05. it was observed that in both groups of general and regional anesthesia, the level of AST, ALT, and ALP enzymes was significantly elevated post-operative compared to pre-operative with (P=0.000), especially in the level of ALT enzyme. The current study indicated that both general and regional anesthesia caused increased liver enzymes. عوامل وأنواع التخدير قد تؤدي إلى تدهور وظائف الكبد. لذلك، من المهم اختيار أدوية التخدير ذات السمية الكبدية الأقل. يتم ملاحظة ارتفاع مستويات ناقلة الأمين في الدم، وناقلة أمين الألانين ، والفوسفاتيز القلوي بشكل متكرر بعد العمليات الجراحية، سواء تم إجراؤها تحت التخدير العام أو النخاعي (المنطقي). ولذلك هدفت الدراسة إلى دراسة ومقارنة التغيرات في إنزيمات الكبد بعد التخدير العام والتخدير النخاعي. تم استخدام ورقة المراقبة للحصول على بيانات من المرضى ثم تحليلها إحصائيًا باستخدام إصدار البرنامج الإحصائي. (SPSS) (23) تم تحديد اختلاف كبير في تغير مستويات إنزيمات الكبد بقيمة p <0.05. وقد لوحظ أنه في كلا المجموعتين تحت التخدير العام والنخاعي، كان مستوى إنزيمات ناقلة الأمين في الدم ، ناقلة أمين الألانين ، والفوسفاتيز القلوي مرتفعاً بشكل ملحوظ بعد العملية مقارنة مع ما قبل العملية مع (P=0.000)، وخاصة في مستوى إنزيم ALT. أشارت الدراسة الحالية إلى أن التخدير العام والإقليمي تسبب في زيادة إنزيمات الكبد.